The Controlling Nutritional Status (CONUT) Score Predicts Post-operatory Risks and Prognosis in Patients With Surgically Treated Colon Cancer: A Retrospective Study - Cozzani, Federico; Ricchiuto, Matteo; Virgilio, Edoardo; Viani, Lorenzo; Rossini, Matteo; Pedrazzi, Giuseppe; Rio, Paolo Del (Anticancer research, 2024)
The Controlling Nutritional status (CONUT) score, a valuable tool evaluating the preoperative conditions of patients from a nutritional point of view, has been successfully adopted for a plethora of malignancies including colorectal cancer (CRC). However, since rectal cancer has characteristics that differ from colon cancer (CC) and because, as of 2024, investigations targeted to surgical CC patients are lacking in the pertinent literature, we decided to assess the predictive role of this scoring system in relation to postoperative course and survival of surgical patients affected only by this malignancy. However, as of 2024, the existing literature on CONUT has typically treated colorectal cancer (CRC) as a single homogeneous entity, often combining results for both colon cancer (CC) and rectal cancer (RC). Since CC differs from RC in pathobiology, prognosis and treatment, we preferred to investigate CONUT in patients affected with CC in order to corroborate or refute the current knowledge on this score system when applied to CRC. With this stated aim, we proceeded to assess the predictive role of CONUT in relation to postoperative course and prognosis of patients who underwent CC surgery only. We retrospectively analyzed data from 341 CC patients who underwent surgery at our Hospital between 2013 and 2018. Starting from serum measurements of lymphocytes, total cholesterol and albumin we used a simplified two-tier CONUT classification in order of increasing severity: high (score ≥3) and low score (scoring <3). On equal staging class and other clinicopathological terms, compared to their high score counterpart, low CONUT subjects went through postoperative complications (both nonsurgical and surgical ones) less frequently, shorter mean hospital stay (11.2 versus 15 days) and more favorable survival (both overall and disease-free survival) with statistical significance. In the light of our results, we encourage to systematically resort to the CONUT score classification in all CC patients scheduled for a curative surgery. Preoperative correction of CONUT parameters through artificial nutrition or other measures appears mandatory as it can drastically improve the postoperative course as well as the long-term prognosis of these subjects.